DOSE-DEPENDENT EFFECTS OF ORAL ADMINISTRATION OF ORANGE JUICE ON EPIDIDYMAL SPERM RESERVE AND SEMEN QUALITY IN ADULT MALE RABBITS - Chiroma, Mbursa; Nuhu, Mapida Agabus; Chiroma, Kwaru Mbursa; Chiroma, Ijuptil; Sambo, Mubarak; Bello, Maryam Suleiman; Aisami, Mustapha Muhammad; Wakil, Abubakkar Muhammad; Madziga, Hannah A.; Arastus, William Arastus (FUDMA Journal of Sciences, 2026)
Citrus sinensis (sweet orange) is rich in vitamins, flavonoids, and bioactive compounds with antioxidant and immunomodulatory properties, which may influence growth performance, haematological parameters, and male reproductive function. This study evaluated the effects of graded doses of Citrus sinensis juice on growth performance, haematology, immune response, and epididymal sperm reserve in adult male rabbits. A total of twenty (20) rabbits were assigned to control, low (3 ml), medium (5 ml), and high (10 ml) juice dose groups and treated for six weeks. Body weight, average daily gain, haematological indices, white blood cell counts, and epididymal sperm parameters were assessed. Administration of Citrus sinensis juice resulted in a dose-dependent increase in body weight gain and average daily gain, particularly in the medium and high-dose groups, although differences were not statistically significant (p > 0.05). Haematological parameters, including packed cell volume and haemoglobin, remained stable, while white blood cell counts increased significantly (p < 0.05) in medium and high-dose groups, indicating enhanced immune activity without pathological lesions. Epididymal sperm reserve and morphometric indices exhibited trends toward improvement at higher doses, consistent with the antioxidant-mediated protection of spermatozoa; however, these changes were generally not statistically significant (p > 0.05). Some variability in sperm motility and morphometric parameters suggests dose-dependent and individual physiological responses. Citrus sinensis juice supplementation may support growth, maintain haematological stability, enhance immune function, and potentially improve male reproductive parameters in rabbits. Observed variability underscores the need for further studies to optimize dosing and clarify mechanisms of action.